The probability distribution of hourly rainfall for Kelantan River basin - Nur Nadia Faziera, Abdul Ghani (2017)
Flood is a natural disaster that caused by the climatological factors which is climate factors, rainfall distribution, winds movements and also the topography of the place. Kelantan River Basin (KRB) frequently affected by flooding events. The excessive rainfall is one of the main cause which can leads to the flash flood or monsoon flood. Then, poor design and management of the urban stormwater system also contribute to the flooding in that catchment area and lastly uncontrolled logging or deforestation were widespread in KRB area also cause flooding. The objectives of this study is to analyse the hourly annual maximum rainfall data from year 1980 until 2016 using probability distribution such as Log-normal and Gumbel distribution and then identify the most appropriate method of probability distribution in KRB. Total of 15 stations that analyse by using annual maximum series of hourly rainfall data. Result of the goodness-of-fit test shows that Lognormal fit better than Gumbel distribution for both Chi-square and Anderson-Darling test. For the estimation of average recurrence interval (ARI), the ARI estimated by Gumbel distribution is higher than Lognormal distribution at larger return period. However, based the goodness of fit test, Lognormal distribution is recommended as the best fit model of overall stations to fit hourly rainfall depth for Kelantan River basin.